Starch and protein sources in elephantgrass-based diets for lactating dairy cows (Scientia Agricola, 2002)
Ruminant performance may be improved due to association of specific energy and protein supplemental sources by matching nutrient degradation rates on diets. This work aimed to analyze the effects of corn grain processing, concentrate levels and protein sources on nutrient digestibilities, ruminal fermentation parameters, and performance of lactating holstein cows. Treatments were: corn silage with high concentrate level containing soybean meal and finelly ground corn (FGC); green chopped elephant grass (CEG) with high concentrate level containing soybean meal and FCG; CEG with low concentrate level containing soybean meal and FCG; CEG with high concentrate level containing soybean meal and steam flaked corn (SFC) (360 g L-1) and CEG with high concentrate level containing fish meal and SFC. The trial was set up in a 5 x 5 latin square design. Overall nutrient digestion, ruminal parameters and milk yield were improved with SFC plus soybean concentrate associated to elephant grass rations. Performance of group fed CEG added with SFC and soybean meal was comparable to the group fed corn silage based ration. Low concentrate ration level or the addition of fish meal did not improve ruminal fermentation, leading to reduced animal performance. In grazing trials with elephant grass, dairy cows present better efficiency when energy availability is enhanced at the ruminal level . The additional energy supply may be achieved by either increasing concentrate level or by altering ruminal starch degradability.